2016
DOI: 10.1111/jan.12978
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tailored patient education on adherence of patients with chronic myeloid leukaemia to tyrosine kinase inhibitors: a randomized multicentre intervention study

Abstract: Tailored patient education improved the medication adherence of patients with chronic myeloid leukaemia. Without this, adherence behaviour tended to decline. Personal communication with a nurse proved to be an essential part of adherence support and should not be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 29 publications
1
53
1
Order By: Relevance
“…Other quantitative studies using a questionnaire found percentages of nonadherent CML patients ranging from 0% to 47%. 11,12,19,23,30,[34][35][36][37][38][39][40][41] Differences in the extent of nonadherence in studies are a well-known phenomenon in adherence research and relate to the drug, follow-up period and differences in measurement and calculation of adherence. 9,42 In the present study, a self-composed question was used to measure nonadherence ("How often do you not take your CML medicine?").…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other quantitative studies using a questionnaire found percentages of nonadherent CML patients ranging from 0% to 47%. 11,12,19,23,30,[34][35][36][37][38][39][40][41] Differences in the extent of nonadherence in studies are a well-known phenomenon in adherence research and relate to the drug, follow-up period and differences in measurement and calculation of adherence. 9,42 In the present study, a self-composed question was used to measure nonadherence ("How often do you not take your CML medicine?").…”
Section: Discussionmentioning
confidence: 99%
“…9,42 In the present study, a self-composed question was used to measure nonadherence ("How often do you not take your CML medicine?"). In the other studies, 11,12,19,23,30,[34][35][36][37][38][39][40][41] alternative questionnaires were used to measure medication adherence. Although the differences in measurements make it difficult to compare the results of studies, it is clear that a considerable number of CML patients have difficulties with adhering to their medication regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nilotinib was approved by FDA as first and only CML therapy with Treatment-free Remission data in its label in 2017. Though nilotinib has achieved good tolerability and high potency, the emerging vascular adverse effects have limited its use as front-line therapy for CML (5)(6)(7)(8)(9). Here, we aimed to investigate the cellular mechanisms involved and to identify a therapeutic strategy to alleviate nilotinib-exacerbated atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%